PENERAPAN SISTEM SPRAY SEMI OTOMATIS PADA INDUSTRI KECIL BUDIDAYA JAMUR TIRAM - Aribudiman, I. N.; Adi Atmika, I. K.; Sri Komaladewi, A. A. I. A. (Buletin Udayana Mengabdi; Vol 15 No 2 (2016): Jurnal Udayana Mengabdi, 2016)
Ayu Suta mushrom group is a business group of farmers mushroom located in the village of Batubulan- Gianyar. Mushroom production is still only oyster mushroom, yields a simple packed with simple plastic bag. This business group has problems related to the efficiency and productivity which these problems are caused by the system is still conventional sterilization with small capacity and lack of system or mechanization maintaining the temperature and humidity incubation chamber messelium in conditions suitable for oyster mushrooms. Then the human resources with an educational background which is still low. Objectives and outcomes of the activities designed are: 1) generate system or mechanization of the process of regulating the temperature and humidity of the room enlargement messelium, which is equipped with a spray of water or fog semi automatic, 2) provide knowledge about management, safety and product quality control in relation the application of the system or mechanization. Settlement system problems or methods offered in this program is to replace the equipment by designing the system or spray semi-automatic mechanization is also equipped with indicators of temperature and humidity. After designing mechanization water sprayer, then began prepared materials and tools, and the first activity was implemented in partner dated August 27 2015, oyster mushroom cultivation place Ayu Suta in Batubulan Gianyar-Bali. Activities started with help clean
Keywords: sterilization, a conventional, automatic spray, efficiency, productivity